Pemberdayaan Masyarakat melalui Pelatihan Videografi sebagai Strategi Pengembangan Promosi Wisata Pantai Kutang - Albab, Ulil; Inayah, Karimatul; Saputra, Surya Agung Agan; Huda, Muflikhul (Dharma: Jurnal Pengabdian Masyarakat, 2025)
The strategy of using video media is very powerful in today's technological era. However, the current problem is the lack of skills and abilities in producing and developing videos into an interesting media. Thus, the availability of adequate basic knowledge and skills in editing and videography is very important, especially in efforts to advance promotion in the field of tourism. This research was conducted with a qualitative approach using data collection techniques: interviews, observations, documentation, and questionnaires. With this method, it is expected to obtain concrete data that is in accordance with the needs of the research carried out in Labuhan Brondong Lamongan village. After the data was collected, it was then analyzed using a qualitative descriptive method. The results of community service show that this activity has a positive impact on residents, managers, government, and the wider community. This activity is also able to empower the community in developing the promotion of Kutang Beach Tourism in Labuhan Brondong Lamongan Village.